A new cavitation model for simulating steady and unsteady cavitating flows. (1st April 2023) - He, Jie; Li, Changjun; Jia, Wenlong; Qiu, Bolin; Yang, Fan; Zhang, Caigong
Abstract: Cavitation is a widespread hydrodynamic phenomenon. Accurate prediction of cavitating flow is beneficial to the design and maintenance of the hydrodynamic machinery. A new cavitation model reducing the number of parameters needed to obtain satisfactory results is presented and validated. Based on the multiphase flow equation, the mass transfer due to cavitation is expressed as a source term in the gas-phase continuity equation. The mass transfer rate is derived from the assumption that the number of cavitation nuclei per unit volume in the mixture varies linearly with the vapor volume fraction during the evaporation stage. The mass transfer rate also incorporates the simplified Rayleigh–Plesset equation and the critical radius of cavitation nuclei. The new cavitation model considers the influence of non-condensable gas and the molar density of non-condensable gas is the only physical parameter that must be specified. The cavitating flow over a hydrofoil, cavitating flow in a sharp-edged orifice, and the unsteady cavitating flow in a venturi tube were predicted to verify the validity of the new cavitation model. The simulation results of the new model are in good agreement with the experimental results. The new cavitation model predicts cavitation regions and periodic unsteady cavitating flows. Highlights: A new cavitation model applicable to various cavitation phenomena is presented. The content of non-condensable gas should be specified in the cavitation model. The cavitating flow over a hydrofoil, cavitating flow in a sharp-edged orifice, and the unsteady cavitating flow in a venturi tube were simulated.